Anesthesia Management of a Pregnant Patient with Idiopathic Intracranial Hypertension and Sepsis Who Needs Emergency Cesarean Section: A Case Report - Ahmed Maher Ibrahim Hashey (Dubai Medical Journal, 2023)
Idiopathic intracranial hypertension (IIH) is a rare neurological disorder, characterized by raising intracranial pressure of unknown reason, increased cerebrospinal fluid pressure without changes in its composition, and usually it is presented by headache, papilledema. In this report, we will discuss the anesthesia management of cesarean section for a 31-year-old, morbidly obese patient (body mass index = 42 kg/m2), pregnant at 37 weeks, with IIH along with sepsis.